Connecting Art and the Brain: An Artist's Perspective on Visual Indeterminacy - Pepperell, Robert (Frontiers in Human Neuroscience, 2011)
In this article I will discuss the intersection between art and neuroscience from the perspective of a practicing artist. I have collaborated on several scientific studies into the effects of art on the brain and behaviour, looking in particular at the phenomenon of ‘visual indeterminacy’. This is a perceptual state in which subjects fail to recognise objects from visual cues. I will look at the background to this phenomenon, and show how various artists have exploited its effect through the history of art. My own attempts to create indeterminate images will be discussed, including some of the technical problems I faced in trying to manipulate the viewer’s perceptual state through paintings. Visual indeterminacy is not widely studied in neuroscience, although references to it can be found in the literature on visual agnosia and object recognition. I will briefly review some of this work and show how my attempts to understand the science behind visual indeterminacy led me to collaborate with psychophysicists and neuroscientists. After reviewing this work, I will discuss the conclusions I have drawn from its findings and consider the problem of how best to integrate neuroscientific methods with artistic knowledge to create truly interdisciplinary approach.